2007
DOI: 10.1152/ajpendo.00274.2006
|View full text |Cite
|
Sign up to set email alerts
|

PGJ2-stimulated β-cell apoptosis is associated with prolonged UPR activation

Abstract: Chambers KT, Weber SM, Corbett JA. PGJ2-stimulated ␤-cell apoptosis is associated with prolonged UPR activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
(102 reference statements)
1
16
0
Order By: Relevance
“…While the increase in tunicamycin-induced death of RINm5F cells expressing UPR transducer mutants may appear to be somewhat attenuated when compared with the increase in death in the corresponding MEFs, it is the expected increase in the level of RINm5F cell death when the 60% transfection efficiency of the UPR transducer mutants is taken into account in these assays. These findings, which support previous studies indicating that UPR-mediated cell death is enhanced in the absence of a functional PERK response (23,33), provide direct evidence that cytokine-induced death can occur independent of UPR activation, as deletion of either PERK or IRE1␣ or expression of the S51A eIF2␣ mutant does not alter the levels of death in response to cytokine treatment.…”
Section: Diabetes Vol 57 January 2008supporting
confidence: 89%
See 3 more Smart Citations
“…While the increase in tunicamycin-induced death of RINm5F cells expressing UPR transducer mutants may appear to be somewhat attenuated when compared with the increase in death in the corresponding MEFs, it is the expected increase in the level of RINm5F cell death when the 60% transfection efficiency of the UPR transducer mutants is taken into account in these assays. These findings, which support previous studies indicating that UPR-mediated cell death is enhanced in the absence of a functional PERK response (23,33), provide direct evidence that cytokine-induced death can occur independent of UPR activation, as deletion of either PERK or IRE1␣ or expression of the S51A eIF2␣ mutant does not alter the levels of death in response to cytokine treatment.…”
Section: Diabetes Vol 57 January 2008supporting
confidence: 89%
“…In contrast, if the UPR participates in cytokine-mediated damage, then inactivation of UPR transducer activity would be expected to enhance cell death. We have previously shown that inhibition of PERK enhances caspase-3 activation in response to PGJ 2 (33), and Scheuner et al (23) demonstrated a 57% increase in tunicamycin-induced apoptosis of MEFs expressing a S51A mutation. Consistent with this hypothesis, there is no difference in the levels of cell death in wild-type, PERK Ϫ/Ϫ , S51A (A/A), and IRE1␣ Ϫ/Ϫ MEFs following a 24-h incubation with IL-1 and IFN-␥.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As shown in other systems, such factors could also induce Ire1 activation and other UPR components in certain cell types (17,(43)(44)(45)(46)(47)(48). A further cause for IRE1 or UPR activation may be to support cell proliferation (clonal expansion) that follows antigen receptor gene rearrangement in B and T cells.…”
Section: Cd8mentioning
confidence: 91%